Imaginiert und real, erschaut und erdacht : Literarische Werke von und über Christen in Ägypten. - Behlmer, Heike (Göttinger Orientforschungen. Syriaca., 2018)
With the attacks by Islamic fundamentalists against Egyptian Copts, Christianity in Egypt suddenly made headlines around the world again. Coptologists and the science of the Christian Orient, on the other hand, have been trying to research this faith community for a long time. Martin Tamcke's and Heike Behlmer's anthology approaches the subject from a different perspective: the articles provide an overview of the work and life of Coptic writers, trace the Copts in modern crime novels, present Coptic migration literature and deal with historical aspects of the subject of Coptic studies. There are also studies on travel reports, works by foreign authors who dealt with the Copts in one way or another, such as Erhart Kästner's book about his captivity in the Egyptian desert, but also on the Coptic references to an Ethiopian saint's story and reports by German missionaries. The often unusual perspectives make the world of the Copts accessible in a new way and show it as part of Egyptian culture, literary and migration history as well as the history of European reception of Coptic reality, thus helping to protect our image of the Copts from being narrowed down.